Handicaps associated with incontinence: implications for management. Issue 3 (September 1990) - McGrother, C W; Jagger, C; Clarke, M; Castleden, C M
Abstract : STUDY OBJECTIVE–The aim was to explore the relationship between dementia, impairment of mobility, and incontinence and the implications for management. DESIGN–The study was a survey of a sample population drawn from a general practice register. SETTING–A large general practice serving the entire population of Melton Mowbray, Leicestershire, UK. PARTICIPANTS–Of 1329 persons aged 75 or over, 1203 (90%) took part in the survey. Of non-responders, refusers accounted for 5%, deaths 4%, and failure to trace 1%. MEASUREMENTS AND MAIN RESULTS–12% of the population complained of incontinence. No more than 24% of these cases were demented. Dementia and isolated locomotor problems were significantly associated with presence of incontinence, but 31% of cases were completely free of either problem. A minimum estimate of 56% of cases of incontinence were considered to be due to local physical disorders of the bladder. CONCLUSIONS–A search for local disorders causing incontinence is important, and more attention should be paid to the management of locomotor problems and possibly depression in the relief of incontinence.